Development of a multifactor authentication result checker system through GSM - Famutimi, Rantiola; Ozichi, Emuoyibofarhe; Abiodun, Akinpelu; Ishaya, Gambo (Multifactor Authentication System, 2020)
How SMS Works ;Newyork Institute of Technology